Determining the Effectiveness of Self-Awareness Skill Training on Reducing High-Risk Behaviors Associated with the Opposite Sex Addict - Farshad Zarie; Hamid Khakbaz; Houryeh Karami (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The aim of this study was to determine the effectiveness of self-awareness skill training on the reduction of high-risk behavior in opposite sex relationship among addicted men. Method: The research method was semi-experimental with pre-test, post-test control group. The study sample was male addicts in Kermanshah. They were selected from four centers of addiction by sampling method. 40 people were selected and randomly replaced into the experimental and control group. Self-awareness skills group training on the experimental group was administered. One week after the training test was taken from them. Results: The finding represent significant mean difference between experimental group and control group high-risk behaviors. Conclusion: Results indicated that self-awareness skill training can reduce high-risk sexual behavior among the addicts.